1962
DOI: 10.2118/168-pa
|View full text |Cite
|
Sign up to set email alerts
|

Stresses Around a Wellbore Due to Internal Pressure and Unequal Principal Geostatic Stresses

Abstract: A three-dimensional photoelastic study was made to determine the stress state around the wall and bottom of a well bore due to fluid pressure with~n the wellbore and unequal principal geostatzc stresses.Models simulating the well bore were made from a phthalic anhydride-cured epoxy resin. The froz~n stress technique of three-dimensional photoelastzcity was used to determine the stresses within the model. Two separate problems were solved:(1) hydrostatic pressure on all sides of the model with the exception of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1967
1967
2001
2001

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Elastic stress data from ... model differed only slightly in magnitude from the stresses indicated by Galle and Wilhoit (1962). The shape of the applied loading curve is almost exactly the same as that obtained from the acrylic model, except that the percentage concentration of the applied stress ahead of the ad-vancing tunnel is slightly lower and this region of stress concentration is not as extensive.…”
Section: Granite Modelsupporting
confidence: 51%
See 3 more Smart Citations
“…Elastic stress data from ... model differed only slightly in magnitude from the stresses indicated by Galle and Wilhoit (1962). The shape of the applied loading curve is almost exactly the same as that obtained from the acrylic model, except that the percentage concentration of the applied stress ahead of the ad-vancing tunnel is slightly lower and this region of stress concentration is not as extensive.…”
Section: Granite Modelsupporting
confidence: 51%
“…The directions of the principal stress changes r~mained essentially fixed (table 7; figs. 16A, 1 n Stresses estimated from photoelastic studies by Galle and Wilhoit (1962), in a smaller but similarly loaded plastic block ahead of a 3.18-cm-(1.25 in.) diameter bore, are in good agreement with the stresses monitored by the probe for a 1.50-tunnel-diameter interval between the probe and the tunnel face ( fig.…”
Section: Acrylic Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, effects from removal of deviatoric and total stresses, termed`block sampling' by Baligh et al (1987), will lead to some disturbance. Also, shear distortion as a result of base heave may cause damage as the borehole is made (Galle & Wilhoit, 1962;Lefebvre & Poulin, 1979). A number of investigators have shown that sampling disturbance of soft clays leads to a reduction in mean effective stress (Hight, 1986;Clayton et al, 1992).…”
Section: Bothkennar Claymentioning
confidence: 99%